THE EFFECTIVENESS OF DIGITAL POPULATION IDENTITY IMPLEMENTATION IN BANDUNG CITY - Rahmadanita, Annisa (Registratie, 2024)
The Ministry of Home Affairs of Indonesia has set up a 25% of Digital Population Identity (DPI) coverage by 2023, and 30 percent in 2024. Unfrotunately, underachievement occured in some areas. This research assessed the effectiveness of the DPI program in Bandung City using a quasi-qualitative method. The commitment of regional leaders and Civil Servants, as well as an organized division of tasks was found adequate. The program has covered key groups of society, including Civil Servants, students, and high school/vocational students. Bandung City has managed to acheive the predtermined target, with proper outreach and apporach throguh online and offline modes. The underachievement of DPI program could be tirggered by unclear measurement indicators and inadequate community outreach and education. This research concludes that DPI program in Bandung City has been relatively effective despite some challenges.Keywords: Program Effectiveness, Digital Population Identity, Population Documents, Digitalization of Public Services.